2011
DOI: 10.1002/jmr.1047
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of molecular recognition of STAT3 SH2 domain inhibitors through molecular simulation

Abstract: Signal transducer and activator of transcription 3 (STAT3) is an anti-cancer target protein due to its over-activation in tumor cells. The Tyr705-phosphorylated (pTyr) STAT3 binds to the pTyr-recognition site of its Src Homology 2 (SH2) domain of another STAT3 monomer to form a homo-dimer, which then causes cellular anti-apoptosis, proliferation, and tumor invasion. Recently, many STAT3 SH2 dimerization inhibitors have been discovered via both computational and experimental methods. To systematically assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 46 publications
0
35
0
Order By: Relevance
“…For example, the number, document type, and abstract of the available references can often allow us to bin series with respect to their priority for follow-up. The essential roles of chemistry in high-throughput screening triage Perspective ≥90%: Compounds that are greater than 90% similar; Biol: Compounds that were reported in a 'biological study' from a journal article [155,[159][160][161][162][163][164][165][166][167][168][169][170][171][172]; Exact: Exact substructure found; Sources: Commercial sources of exact compound. 6 [160][161][162][163][164] [165] [156,166,167,168,169] [ 168,169,170,171,172,173] future science group Perspective Dahlin & Walters otherwise following up on HTS results.…”
Section: Future Science Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the number, document type, and abstract of the available references can often allow us to bin series with respect to their priority for follow-up. The essential roles of chemistry in high-throughput screening triage Perspective ≥90%: Compounds that are greater than 90% similar; Biol: Compounds that were reported in a 'biological study' from a journal article [155,[159][160][161][162][163][164][165][166][167][168][169][170][171][172]; Exact: Exact substructure found; Sources: Commercial sources of exact compound. 6 [160][161][162][163][164] [165] [156,166,167,168,169] [ 168,169,170,171,172,173] future science group Perspective Dahlin & Walters otherwise following up on HTS results.…”
Section: Future Science Groupmentioning
confidence: 99%
“…This apparent disregard or lack of knowledge of the preceding literature is not an isolated phenomenon. The two other most recent publications, references [165] and [169], make no mention of PAINS and no mention of the work on similar compounds reported in references [155,[165][166][167][168] and [167][168][169][170][171][172], respectively (admittedly, reference [169] does reference an earlier paper by that describes the protocol for detecting compounds capable of redox interference [81]).…”
Section: Future Science Groupmentioning
confidence: 99%
“… 20 , 21 Superimposition of structures revealed that STAT3′s SH2 domain structure is not significantly altered upon phosphopeptide binding. 22 Thus, we reasoned that the unphosphorylated STAT5 structure (PDB: 1Y1U) is suitable for in silico -based drug design. Analogous to the canonical pY-SH2 domain binding, the STAT5 pY likely docks proximal to the conserved R618 (βB strand), making H-bonding/electrostatic interactions with nearby polar residues, K600 (αA), T628 (βC), and S622 (βB and βC) Figure 2 A.…”
mentioning
confidence: 99%
“…The p -cyclohexylbenzyl group places the cyclohexyl group deep within the hydrophobic pY-X pocket. 34 …”
Section: Resultsmentioning
confidence: 99%